2017
DOI: 10.1542/peds.2016-4131
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Use of Opioids During Pregnancy and Congenital Malformations: A Systematic Review

Abstract: CONTEXT Opioid use and abuse have increased dramatically in recent years, particularly among women. OBJECTIVES We conducted a systematic review to evaluate the association between prenatal opioid use and congenital malformations. DATA SOURCES We searched Medline and Embase for studies published from 1946 to 2016 and reviewed reference lists to identify additional relevant studies. STUDY SELECTION We included studies that were full-text journal articles and reported the results of original epidemiologic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
115
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(123 citation statements)
references
References 83 publications
6
115
1
1
Order By: Relevance
“…Substantial increases in prescription opioid use among pregnant women have been observed, and the prevalence of opioid dependence and illicit opioid use among pregnant women has increased over the past decade . Among parturients in a tertiary facility in the United States, the prevalence of opioid dependence increased by 127% between 1998 to 2011, and the proportion of pregnant women filling opioid prescriptions for opioid dependence increased by 250% between 1995 and 2009 in a cohort study . Calls to an Australian obstetric drug information service related to oxycodone increased significantly between 2007 and 2016, rising from 3.8% of psychotropic/addictive‐related calls in 2007 ( n = 395) to 6.0% of calls in 2016 ( n = 897) (D. Kennedy, personal communication).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Substantial increases in prescription opioid use among pregnant women have been observed, and the prevalence of opioid dependence and illicit opioid use among pregnant women has increased over the past decade . Among parturients in a tertiary facility in the United States, the prevalence of opioid dependence increased by 127% between 1998 to 2011, and the proportion of pregnant women filling opioid prescriptions for opioid dependence increased by 250% between 1995 and 2009 in a cohort study . Calls to an Australian obstetric drug information service related to oxycodone increased significantly between 2007 and 2016, rising from 3.8% of psychotropic/addictive‐related calls in 2007 ( n = 395) to 6.0% of calls in 2016 ( n = 897) (D. Kennedy, personal communication).…”
Section: Methodsmentioning
confidence: 99%
“…The literature evaluating the teratogenicity of opioid use in early pregnancy is limited (Table ), and studies frequently have weaknesses with outcome and exposure measurement . In a large Norwegian population‐based cohort study, Nezvalová‐Henriksen and colleagues found no statistically significant associations between neonatal codeine exposure and congenital malformations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that the use of opioids during pregnancy increases the risk for birth abnormalities such as neural tube defects, gastroschisis, congenital heart defects, clubfoot, and neonatal abstinence syndrome . However, data on use of opioids during pregnancy and delivery outcomes is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…4,[8][9][10][11] Several studies have shown that the use of opioids during pregnancy increases the risk for birth abnormalities such as neural tube defects, gastroschisis, congenital heart defects, clubfoot, and neonatal abstinence syndrome. 8,[12][13][14] However, data on use of opioids during pregnancy and delivery outcomes is scarce. A Norwegian study observed that self-reported codeine used anytime during pregnancy was associated with an increased risk for planned caesarean sections, and codeine used in the third trimester of pregnancy was associated with acute caesarean sections and postpartum haemorrhage.…”
Section: Introductionmentioning
confidence: 99%